The role of the Mediterranean Diet in preventing the development and complications of lifestyle diseases – a Review - Alicja Kapciak; Julia Górny; Rafał Kaczorowski; Aleksandra Pelczarska; Michał Janiszewski; Marcin Komorowski; Tomasz Forenc; Jaromir Hunia; Jonasz Jurek (Quality in Sport)
Introduction The Mediterranean diet, inspired by traditional dietary habits of the Mediterranean region, exhibits anti-inflammatory and protective effects, reducing the risk of civilization diseases such as obesity, type 2 diabetes, and cardiovascular disorders. This diet is characterized by a high intake of plant-based foods, olive oil, and moderate consumption of fish and dairy products. These components provide unsaturated fatty acids, polyphenols, and antioxidants, which positively impact metabolic health and lower the risk of chronic diseases. In the face of the global obesity epidemic and an increasing number of individuals affected by lifestyle-related diseases, the Mediterranean diet offers a promising tool to support a healthy lifestyle.